CHARMM‐GUI ligand reader and modeler for CHARMM force field generation of small molecules. Issue 21 (11th May 2017) - Kim, Seonghoon; Lee, Jumin; Jo, Sunhwan; Brooks, Charles L.; Lee, Hui Sun; Im, Wonpil
Abstract : Reading ligand structures into any simulation program is often nontrivial and time consuming, especially when the force field parameters and/or structure files of the corresponding molecules are not available. To address this problem, we have developed Ligand Reader & Modeler in CHARMM‐GUI. Users can upload ligand structure information in various forms (using PDB ID, ligand ID, SMILES, MOL/MOL2/SDF file, or PDB/mmCIF file), and the uploaded structure is displayed on a sketchpad for verification and further modification. Based on the displayed structure, Ligand Reader & Modeler generates the ligand force field parameters and necessary structure files by searching for the ligand in the CHARMM force field library or using the CHARMM general force field (CGenFF). In addition, users can define chemical substitution sites and draw substituents in each site on the sketchpad to generate a set of combinatorial structure files and corresponding force field parameters for throughput or alchemical free energy simulations. Finally, the output from Ligand Reader & Modeler can be used in other CHARMM‐GUI modules to build a protein‐ligand simulation system for all supported simulation programs, such as CHARMM, NAMD, GROMACS, AMBER, GENESIS, LAMMPS, Desmond, OpenMM, and CHARMM/OpenMM. Ligand Reader & Modeler is available as a functional module of CHARMM‐GUI athttp://www.charmm-gui.org/input/ligandrm . © 2017 Wiley Periodicals, Inc. Abstract : Superposition of 24 TIBO derivatives (different colors) generated by CHARMM‐GUI Ligand Reader and Modeler with HIV‐1 RT (magenta) and the scaffold atoms (orange).